Modeling the density at Merapi volcano area, Indonesia, via the inverse gravimetric problem - Tiede, C.; Camacho, A. G.; Gerstenecker, C.; Fernández, J.; Suyanto, I. (Geochemistry, geophysics, geosystems : G3, 2005)
Merapi is a high‐risk andesitic volcano in Central Java, Indonesia. Very little information is known about the detailed regional density structure around Merapi and its neighbor volcano Merbabu. We compute a subsurface three‐dimensional (3‐D) model of anomalous density for the volcanoes Merapi and Merbabu in Central Java, Indonesia, by inversion of the gravity field. As input for the inversion methodology, gravity observations from 443 points, whose 3‐D coordinates are determined by GPS, are used. The inversion algorithm is based on an explorative approach to fit a least squares condition, including a balancing factor between the minimization of the residuals and the anomalous mass. A mean density about 2242 kg/m3 for the region of Merapi and Merbabu has been computed by least squares adjustment. Results of the inversion show major low‐density contrasts up to −242 kg/m3 and positive structures about +264 kg/m3, referred to the determined mean density. A density anomaly (relative high) with densities up to +264 kg/m3 is connecting the volcanoes in a 152° course from NW to SE and might be built of older basaltic lava. Low‐density contrasts about −242 kg/m could be found in agreement with magnetotelluric and electromagnetic results. Generally, the identified high‐ and low‐density bodies are in agreement with the results of other geophysical methods such as electromagnetic and magnetotelluric prospecting or geological formations and structures. A porosity about 21% is derived for the largest negative density bodies about −242 kg/m3. Furthermore, the density model gives some new information about the controversial origin of a hill formation near Merapi and is also used to discuss the possible existence of a shallow magma chamber, which is also a controversial subject. Generally, the density model serves as basic information for the interpretation of geodetic and geophysical observations and confirms existing results from magnetotellurics, electromagnetics, and seismic data interpretation.